Muscle Synergy Analysis for Stand-Squat and Squat-Stand Tasks with sEMG Signals - Chen, Chao; Gao, Farong; Sun, Chunling; Wu, Qiuxuan (Biometric Recognition, 2018)
Human walking is the composite movement of the musculoskeletal system in lower limbs. The interaction mechanism of the different muscle groups in a combination action is of great importance. To this end, under the stand-squat and squat-stand tasks, the problems of the motion model decomposition and the muscle synergy were studied in this paper. Firstly, the envelopes were extracted from acquired and de-noised surface electromyography (sEMG) signals. Secondly, the non-negative matrix factorization (NMF) algorithm was explored to decompose the four synergistic modules and the corresponding activation coefficients under the two tasks. Finally, the relationship between the muscle synergy and the lower limb movement was discussed in normal and fatigue subjects. The results show that muscle participation of each synergistic module is consistent with the physiological function, and exhibit some differences in muscle synergies between normal and fatigue states. This work can help to understand the control strategies of the nervous system in lower extremity motor and have some significance for the evaluation of limb rehabilitation.